1987
DOI: 10.1677/joe.0.114r001
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Against an Inhibin Subunit Produced by Recombinant Dna Techniques Results in Increased Ovulation Rate in Sheep

Abstract: Seven Merino-Border Leicester cross-bred ewes were immunized with a purified fusion protein, produced by recombinant DNA methods, of the alpha subunit of bovine inhibin. Four animals were immunized with the fusion protein alone and three with a conjugate made by coupling the fusion protein to keyhole limpet haemocyanin (KLH) using glutaraldehyde. Each animal received four injections of the fusion protein over 93 days. The animals were synchronized using progestagen sponges and subjected to laparoscopy for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…Active immunization against INH neutralizes endogenous INH and increases the ovulation rate in mammals [6,7,10,[37][38][39]. The results of the present study showed no significant difference in egg production between birds that were actively immunized against INH and control hens, even though immunization significantly increased the number of preovulatory yellow follicles and significantly increased FSH␤ subunit mRNA content in the anterior pituitary.…”
Section: Discussioncontrasting
confidence: 43%
“…Active immunization against INH neutralizes endogenous INH and increases the ovulation rate in mammals [6,7,10,[37][38][39]. The results of the present study showed no significant difference in egg production between birds that were actively immunized against INH and control hens, even though immunization significantly increased the number of preovulatory yellow follicles and significantly increased FSH␤ subunit mRNA content in the anterior pituitary.…”
Section: Discussioncontrasting
confidence: 43%
“…The α-subunit of ovine inhibin produced in E. coli the by the recombinant DNA method [17] was used as an immunogen. Immunizations were given at a dose of 1 ml of the immunogen (125 µg/ml) in Montanide 888:Marcol 52 (1:9) each time.…”
Section: Inhibin Vaccinementioning
confidence: 99%
“…On the other hand, nondominant follicles would not have these survival mechanisms and would therefore be destined to become atretic. With respect to the potential paracrine role of inhibin on theca androgen production, it is worth mentioning that immunization of animals against inhibin-which produces antibodies that recognize biologically active forms of inhibin-causes an increase in ovulation rate [19]. This suggests that either an action of inhibin on theca cells in vivo is not an absolute requirement for normal follicular development and ovulation or that the inhibin antibodies are not able to compromise an action of inhibin on the theca.…”
Section: Intrafollicular Actions Of Inhibinmentioning
confidence: 99%